2015
DOI: 10.1007/s00383-015-3763-3
|View full text |Cite
|
Sign up to set email alerts
|

Benign liver tumors in children: outcomes after resection

Abstract: Two-third patients with benign liver tumors were managed with surgical excision, which comprised 11% of our resectional practice. Non-anatomical resection whenever feasible can be performed safely and does not compromise the oncological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
4
3
1
1
Order By: Relevance
“…2,21 Haemangioma was the commonest benign liver tumor constituting 70% of all benign tumors in our series this is in comparison with other authors who have reported haemangioma constituting 72% of all the benign tumors in their series. 3 Most of the liver haemangiomas can be safely followed up.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…2,21 Haemangioma was the commonest benign liver tumor constituting 70% of all benign tumors in our series this is in comparison with other authors who have reported haemangioma constituting 72% of all the benign tumors in their series. 3 Most of the liver haemangiomas can be safely followed up.…”
Section: Discussioncontrasting
confidence: 41%
“…This is in comparison with Quresh SS et al, who reported that one third of their patients with benign liver tumors were managed with surgical excision, which comprised 11% of their re-sectional practice over a period of 10 years. 21 They have also reported that there was no mortality in their series and none of their patient had recurrence.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, only 33% of patients with benign lesions were diagnosed by classic imaging criteria. Similarly, Qureshi et al reported that 38% of patients in their series were diagnosed as per radiological features [13]. In contradiction, Kochin et al declared that definitive diagnosis using imaging was achieved in 58.5% of the patients in their study [14].…”
Section: Discussionmentioning
confidence: 93%
“…Karaciğerin benign tümörlerinin cerrahi tedavilerinde anatomik olmayan rezeksiyonun emniyetli bir şekilde yapılabileceği belirtilmiştir (23) . Ancak art arda yapı-lan iki Alman çalışmasında, atipik rezeksiyon yapılan hepatoblastomlu olguların %38'inde rezeksiyon sonrası tümör kaldığı, sonuçların bu hastalarda en kötü olduğu görülmüştür.…”
Section: Rezeksiyonunclassified